The Influence Of Noise, Workload, Length Of Work And Employment Status On Work Productivity Through Work Fatigue Of PT. Indonesia Power UBP Tello In 2024 - Armelani Anggrayni; Atjo Wahyu; Masyitha Muis; Yahya Thamrin; Irwandy; Anwar Mallongi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Objective:This study aims to analyse the direct and indirect effects of noise, workload, work mass and work status on work productivity, with work fatigue as an intervening variable. Methods:The research was carried out on all employees in the PLTD and PLTG units of PLN IP UBP Tello, a total of 84 people, using total sampling for data collection. Data was collected through interviews, noise level measurements using the Decibel X application, fatigue assessments using a reaction timer tool and productivity observation sheets. Data analysis was performed using path analysis with Smart PLS software. Results:The results indicate that work mass (p-value = 0.008), work status (p-value = 0.003) and work fatigue (p-value = 0.000) have a significant direct effect on work productivity. Noise (p-value = 0.549) and workload (p-value = 0.151) have no significant direct effect on work productivity. For indirect effects, noise (p-value = 0.004), workload (p-value = 0.000) and work mass (p-value = 0.035) show significant indirect effects on productivity through work fatigue. However, job status does not have a significant indirect effect on productivity through work fatigue (p-value = 0.320). Conclusions: PT. PLN IP UBP Tello is recommended to identify and fulfill the specific needs of its employees in order to improve job satisfaction and elevate productivity.